The Significance Of Physical Culture And Sports And Their Integration Into The Daily Life Of Students (Texas Journal of Medical Science, 2026)
The article examines the importance of physical culture and sport in the life of modern university students and analyzes the conditions required for their effective integration into students’ daily routines. It is argued that physical culture within higher education should be understood not as an isolated academic subject or occasional exercise, but as a substantial component of personal culture that supports health preservation, psychological resilience, self-regulation, social inclusion, and academic performance. Drawing on current international guidelines and systematic reviews, the paper shows that regular physical activity is associated with reduced risk of chronic noncommunicable diseases, improved mental well-being, lower levels of anxiety, depressive symptoms, and stress, as well as with several positive educational and behavioral outcomes